Psychographic Measures of Service Quality of Family-Style Restaurants - Mellina-Jimenez, Florence Kristina M.; Aldepolla, Jessa Christine C.; Alcachopas, Lilac; Pauliňo, Lucille S.; David, Leonil G.; Galgo, Glinda (Archives of Business Research, 2014)
Understanding overall quality of service, particularly if it regards to fulfilling customers’ needs and exceeding expectations is crucial in food and beverage service operations. The primary purpose of the study was to determine the psychographic measures of service quality of family style restaurants in Davao City. There were a total of one-hundred respondents participated in the study. Demographic characteristics of the respondents were examined to explore effects in the perceived quality of service. Majority of the respondents were male, young professionals. Data were collected by means of validated questionnaires. Using exploratory factor analysis, results revealed three components explaining service quality of family style restaurants which include tangibility, reliability and supply reliability. Findings suggest that preference of family style restaurant is influenced by the provision of service as promised, convenience of the restaurant’s location, and the availability of the staff in handling guests’ requests. While the study found no gender and education based differences, there were marked differences across age groups. Keywords: service quality, psychographic measure, tangibility, reliability, family style restaurants, factor analysis